Living conditions, social exclusion and recidivism among prison inmates - Nilsson, Anders (Journal of Scandinavian studies in criminology and crime prevention, 2003)
This article examines the importance of living conditions for recidivism following release from prison. How do resource deficiencies in different welfare-related areas, such as education, employment, the financial situation, housing, social relations and health, affect the risk for recidivism? How important are deficiencies of this kind by comparison with known risk factors associated with levels of previous involvement in crime? The analyses are based on a representative sample of Swedish prison inmates (n=346). Data on their living conditions were collected at interview and were then linked to data on reoffending within three years of release from prison. The findings show inter alia that problems relating to education and employment, but above all an accumulation of different types of resource problems, are clearly correlated with recidivism. They show further that the effect of living conditions and resource deficiencies on reoffending is primarily felt by those who at the time of interview had not previously served time in prison. One possible interpretation looks to different risk factors to explain the onset and continuation of a criminal career. A prison term serves to reduce the opportunities to lead a conventional life - with a legitimate income - and thereby contributes to marginalisation and social exclusion